Impact of Remittance on Gross Domestic Savings in Nepal - Adhikari, Madan (Nepal Journal of Multidisciplinary Research, 2023)
The Nepalese economy is receiving a steady stream of remittances, but the nation has struggled to reduce poverty, unemployment, and the problem of infrastructure development. Being an underdeveloped nation with a high level of consumption and low levels of capital formation, it is a severe issue that will cause imports to rise even more. This paper examines the impact of remittance on gross domestic savings in Nepal using the Autoregressive distributed lag model. As discovered through the study, remittances are insignificant to gross domestic savings both in the long as well as short run. This contradicts the studies that show a positive and negative relationship between remittance and gross domestic savings. The study also shows that other factor such as gross domestic product affects gross domestic saving positively. It is therefore recommended that the planners and decision-makers should take the high rate of remittance income consumption in the economy seriously and must implement the consumption reduction that leads to increased savings, which contributes to the nation's overall growth and development.